2016
DOI: 10.1186/s12985-016-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C promotes dengue virus replication

Abstract: BackgroundDengue virus (DENV) is a member of the Flaviviridae family, transmitted to human via mosquito. DENV infection is common in tropical areas and occasionally causes life-threatening symptoms. DENV contains a relatively short positive-stranded RNA genome, which encodes ten viral proteins. Thus, the viral life cycle is necessarily rely on or regulated by host factors.MethodsIn silico analyses in conjunction with in vitro kinase assay were used to study kinases that potentially phosphorylate DENV NS5. Pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In addition to MAPKs, curcumin has been demonstrated to modulate the activity of various protein kinases [ 39 , 40 ]. In addition to maintaining physiological homeostasis, PKC has been implicated in the replication of dengue virus [ 41 , 42 ]. Furthermore, PKCδ affects HIV replication via modulation of the post-entry step [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MAPKs, curcumin has been demonstrated to modulate the activity of various protein kinases [ 39 , 40 ]. In addition to maintaining physiological homeostasis, PKC has been implicated in the replication of dengue virus [ 41 , 42 ]. Furthermore, PKCδ affects HIV replication via modulation of the post-entry step [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…PKC phosphorylation of the C viral protein has been described as the key regulator of apoptosis induction during infection [ 25 ], and inhibition of all PKC isoforms affected WNV entry into mosquito cells [ 26 ]. Conversely, DENV replication was enhanced after in vitro inhibition with bisindlolylmaleinmide I (Bis I), a specific chemical inhibitor of classical and novel PKCs [ 17 ]. In our study, both calphostin C and chelerythrine decreased the amount of RNA released to the culture medium and of dsRNA intermediates formation, even though the observed reduction was significantly higher when chelerythrine was used.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this role of PKCs in the control of cell biology, both in silico and in vitro analyses performed with DENV indicated that the flaviviral RNA-dependent RNA polymerase (NS5) contains four potential phosphorylation sites for PKC that are involved in the modulation of the viral replication. Three out of these four sites (Thr302, Ser796, and Ser885, according to DENV2 strain, Genbank AHG23127) are present in WNV, two of them (Thr302 and Ser796) being conserved in all vector-borne flaviviruses [ 17 ]. Phosphorylation of flavivirus NS5 has been widely reported [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of phosphorylation of viral proteins in the viral live cycle has been increasingly recognized, as demonstrated for multiple viruses, including influenza A virus (39), Newcastle disease virus (40), hepatitis C virus (41), dengue virus (42), and Rift valley virus (43), among others. While phosphatases are involved in multiple normal physiological reactions of cells, targeting of their noncatalytic sites, which prevents their interaction with only certain substrates, including viral proteins, may be a viable approach to develop broadly specific antivirals.…”
Section: Discussionmentioning
confidence: 99%